PENERAPAN METODE RAPID APPLICATION DEVELOPMENT DALAM PERANCANGAN SISTEM SIRKULASI ADMINISTRASI DAN PENELITIAN (SIALIM) Di LPPM UNIVERSITAS PAMULANG - Nur, Muhammad; Fathoni, Azhar; Yudansyah, Muhammad Nur Halim; Haryono, Wasis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Pamulang, 2023)
In order to produce superior and competent lecturers, every higher education institution must implement the Tridharma of Higher Education. Tridharma of Higher Education, hereinafter referred to as Tridharma, is the obligation of Higher Education to provide education, research, and community service. (PP-12 of 2012).Archiving is a letter of office work or administrative work that is mostly carried out by every business entity, both in government and private businesses (Surojo, 2006). Archived information is that which is collected and can be accessed and used. (Georgia Archives, 2004). Archives are very important to obtain material or data that can be used as consideration for decision making.At LPPM Pamulang University there is no system for detecting research and service reports so it is still difficult to know which lecturers have done research and service. The goal to be achieved in this research is to develop a desktop-based application that can help overcome the problems experienced by LPPM Pamulang University. In archiving incoming report data, a system must have a goal or objective. The target of the system will determine the required input system and the resulting system output.The RAD method is very suitable to be used to design a system, so it can be easy to arrange a series of systems that are being built. In conducting administrative and research archiving, it is very necessary to have a system role so that it is easy to store and manage data in such a way.